To rewrite the equation \( \frac{4x}{3x - 12} + 3 = 10 \) in two equations joined by "and," we can first isolate the fraction and then represent each part as separate equations. Here is one way to do that:
-
Start with the original equation: \[ \frac{4x}{3x - 12} + 3 = 10 \]
-
Subtract 3 from both sides to isolate the fraction: \[ \frac{4x}{3x - 12} = 7 \]
-
Now, we can split it into two equations: \[ \frac{4x}{3x - 12} = 7 \quad \text{and} \quad 3x - 12 \neq 0 \]
Thus, the rewritten form is: \[ \frac{4x}{3x - 12} = 7 \quad \text{and} \quad 3x - 12 \neq 0 \]